General Features of the Libyan Strategy for Water Resource Management - Abugdera, Ahmed F. (AlQalam Journal of Medical and Applied Sciences, 2024)
Current reports highlight a global water crisis affecting humanity and the environment. Libya, with its limited water resources, relies primarily on groundwater, with agricultural use accounting for 78% of consumption, urban at 12%, and industrial at 10%. This paper assesses the challenges of water scarcity and proposes a Libyan water resource management strategy. It reveals that the depletion of groundwater is largely due to previous political decisions allowing unrestricted well drilling. Without intervention, Libya risks complete resource depletion, leading to significant economic and political costs. The proposed strategy emphasizes the need for a clear water policy and effective management practices. It calls for a reevaluation of agricultural consumption policies to enhance efficiency and promote alternative water sources like desalination and treated wastewater. Additionally, it suggests reprogramming investments in the Great Man-Made River and prioritizing water allocations for the most affected areas. Researchers urge adherence to environmental protection regulations and recommend integrating these insights into the Libyan strategy to mitigate negative impacts effectively. تشير التقارير المحلية والدولية إلى أزمة المياه العالمية التي تؤثر على الإنسانية والبيئة بشكل كبير. وتعتمد ليبيا، بمصادرها المائية المحدودة، بشكل رئيسي على المياه الجوفية، حيث يشكل الاستهلاك الزراعي 78% من إجمالي الاستخدام، والاستهلاك الحضري 12%، والاستهلاك الصناعي 10%. تهدف هذه الورقة إلى دراسة تحديات ندرة المياه واقتراح استراتيجية وطنية لإدارة الموارد المائية في ليبيا. وتبين الدراسة أن الاستنزاف الأساسي للمياه الجوفية يعود بشكل رئيسي إلى قرارات سياسية سابقة سمحت بحفر الآبار دون قيود. وفي غياب استراتيجية شاملة لإدارة الموارد المائية، تواجه ليبيا خطر استنفاد مواردها بشكل كامل، مما سيترتب عليه تكاليف اقتصادية وسياسية كبيرة. تؤكد الاستراتيجية المقترحة على أهمية وضع سياسة مائية واضحة وتبني ممارسات إدارة فعّالة. كما تدعو إلى إعادة تقييم سياسات استهلاك المياه في القطاع الزراعي بهدف تحسين الكفاءة وتشجيع استخدام مصادر بديلة مثل تحلية المياه وإعادة استخدام المياه المعالجة. توصي الاستراتيجية المقترحة بإعادة توجيه الاستثمارات في مشروع النهر الصناعي العظيم وتخصيص المياه بشكل أولوي للمناطق الأكثر تضرراً. ويشدد الباحثون على ضرورة الالتزام بكافة بنود النظام العام لحماية البيئة ولوائحه التنفيذية واللوائح والتصاميم المتعلقة بحماية البيئة، مع مراعاة توصيات هذا التقرير عند إعداد الاستراتيجية الليبية لضمان التحليل السليم وتخفيف الآثار السلبية قدر الإمكان